Personality in Memoirs of a Woman Doctor (1958) by Nawal El-Saadawi - Djoual, Kawther; Djabri, Soumia; Naoumi ,Mohammed (University of Ammar Theledji -Laghouat, 2021)
In a world that has become heavily concerned with the psyche, the study of the humans’ inner worlds comes to the front. This research work aims to present the theme of personality in Memoirs of a Woman Doctor (1958) by Nawal El-Saadawi. The work involves the study of personality in both psychological and literary domains, together they provide a full understanding about the topic helping us to identify the way personality as a theme is portrayed in the novel. This leads to learning the concept of personality in a deep manner, its psychological implications, and the analysis of literary illustrations in the novel. The method used in exploring the research is descriptive analytical. This research study provides important results showing the weaving of events, actions, characters, feelings, and personal development as a means to build a clear image of the personality